Identification and characterization of lipoxygenase (LOX) genes involved in abiotic stresses in yellow horn. - Fang Hu; Yunxiang Zhang; Jinping Guo (PLoS ONE, 2023)
Lipoxygenase (LOX) gene plays an essential role in plant growth, development, and stress response. 15 LOX genes were identified, which were unevenly distributed on chromosomes and divided into three subclasses in this study. In promoter region analysis, many cis-elements were identified in growth and development, abiotic stress response, hormonal response, and light response. qRT-PCR showed that the LOX gene showed tissue specificity in seven tissues, especially XsLOX1, 3, and 7 were relatively highly expressed in roots, stems, and axillary buds. The different expression patterns of LOX genes in response to abiotic stress and hormone treatment indicate that different XsLOX genes have different reactions to these stresses and play diversified roles. This study improves our understanding of the mechanism of LOX regulation in plant growth, development, and stress and lays a foundation for further analysis of biological functions.